Individual tenure and collective contracts - Knut Gerlach; Gesine Stephan (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2005)
The paper analyses the relationship between individual tenure and the application of collective contracts at the firm level, using a multi-level model and a German linked employer-employee data set for the years 1990, 1995 and 2001. The main result is that elapsed tenure is longer in firms applying collective contracts than in companies with individual wage-setting. Thus workers in firms with collective contracts benefit not only from higher wages, but also from higher job stability. Furthermore, we find no significant changes in mean tenure during the nineties as well as stable differences across wage-setting regimes.
Keywords: J51; 330; Betriebszugehörigkeit - Dauer; Firmentarifvertrag; Tarifvertrag; Arbeitsplatzsicherheit; Lohnhöhe